OWNERSHIP CONCENTRATION AND FINANCIAL PERFORMANCE OF LISTED FIRMS IN KENYA: AN ECONOMETRIC ANALYSIS USING PANEL DATA - Mule, Robert Kisavi; Mukras, M.S.; Oginda, Moses N. (European Scientific Journal, ESJ, 2013)
In this study, we use panel methodology comprising 53 firms listed at the Nairobi Securities Exchange to establish the effect of ownership concentration on financial performance of these firms for the period 2007 to 2011. Before empirical estimations were conducted, the data series were subjected to unit root tests to establish their stationarity conditions and where a series is found to be non-stationary at levels, it was differenced until it become stationary. The study findings revealed that on average, firms listed at the Nairobi Securities Exchange enjoy a return on equity and return on assets of about 16.5 percent. The sectors that registered the highest return on equity included insurance, commerce and construction at 20.8 percent, 19.3 percent and 20.1 percent, respectively. On the other hand, the sectors that registered relatively higher return on assets include commerce, telecommunications and manufacturing with average ROA of 23.0 percent, 20.0 percent and 25.4 percent; respectively. The study also found that the highest ownership concentration is 96.310 %, while the lowest is 11.040%, with an average ownership concentration of 64.286 % and variability of 17.292 % implying that the percentage of shares held by those considered as large shareholders range between 96.310 % and 11.040 %, with a mean of 64.286 % and finally the results of correlation analysis revealed non-significant relationship between ownership concentration and performance of firms at the Nairobi Securities Exchange. On the other hand, from the panel regression analysis results, ownership concentration was found to be negatively related to all the three measures of performance in firms listed at the Nairobi Securities Exchange namely ROE, ROA and Tobin’s Q with coefficients of -0.0005, -0.0002 and 0.0057 respectively. The adjusted R squared for the return on equity, return on assets and Tobin’s Q models were 77.32%, 88.52% and 85.94% respectively.